The virtue of sympathy : magic, philosophy, and literature in seventeenth-century England - Lobis, Seth (Yale studies in English., 2014)
"Beginning with an analysis of Shakespeare's The Tempest and building to a new reading of Milton's Paradise Lost, author Seth Lobis charts a profound change in the cultural meaning of sympathy during the seventeenth century. Having long referred to magical affinities in the universe, sympathy was increasingly understood to be a force of connection between people. By examining sympathy in literary and philosophical writing of the period, Lobis illuminates an extraordinary shift in human understanding"--